Cervical Stimulation in the Treatment of Children with Lymphedema of All Four Extremities: A Case Report and Literature Review - Livia Maria Pereira de Godoy; Paula Pereira de Godoy Capeletto; José Maria Pereira de Godoy; Maria de Fátima Guerreiro Godoy (Case Reports in Pediatrics)
Aim. The aim of this study is to report on the use of cervical stimulation as monotherapy to reduce swelling and normalize the size of limbs in two children with lymphedema of all four extremities. Case Presentation. One child also had hemifacial edema. In both cases, the mothers were trained to perform cervical stimulation under professional supervision. The cases of two girls, one of eight months and the other of six months, with primary congenital lymphedema are described. Outcome. After clinical diagnosis, the patients started treatment with cervical stimulation three times per week. The mothers were trained in cervical stimulation and, when the therapy team was confident about the mothers’ ability to perform the technique, the children began to be treated at home. The Godoy & Godoy cervical stimulation technique consists of around 20 to 30 light stroking movements per minute in the cervical region which stimulate the lymphatics. Perimetric measurements were made of the feet, legs, and the hands. Only two points (3 and 6 cm) along the dorsum of the feet and hands and points at 5 cm intervals up the legs starting at the ankle were considered. Today, the children are 5 and 6 years of age, without edema and with a normal life, without limitations, except with respect to precautions against injuries to the limbs and against infections particularly erysipelas. Conclusion. Cervical Lymphatic Therapy as monotherapy is an option in the treatment of primary congenital lymphedema.